AB0662 Flares in systemic lupus erythematosus: Etiology, outcome and prognostic factors. (23rd January 2014) - Teixeira, F.; Peixoto, D.; Costa, J.; Afonso, C.; Araújo, D.
Abstract : Background: Lupus is a chronic, remitting and relapsing autoimmune disorder characterized by unpredictable disease flares and remissions. The rate and the severity of flares during course of treatment are important predictors of disease outcome. An essential part of treating patients with SLE is to try to keep the frequency and intensity of flares to a minimum. Objectives: To determine the flare rate, etiology, outcome and prognostic factors for SLE flares. Methods: One hundred and nine patients with SLE followed by our rheumatology department between 1995 and 2011 were eligible for the study. All patients included fulfilled ACR criteria for SLE. A flare was defined as (according to international consensus for a definition of disease flare in lupus) an increase in disease activity in one or more organ systems involving new or worsening clinical signs and symptoms and/or laboratory measurements. All pre-flare, flare, and post-flare visits were recorded with a SLEDAI score calculated for each visit. The flare rate was calculated by dividing the total number of flares in the cohort by the total follow-up years. We studied 109 patients, 106 female (97.2%) and 3 male (2.8%), with a mean age of 30.2±12.6 years at time of the diagnosis and 40.7±12.4 years in follow-up. In the statistical analysis (fisher exact test and student T test for categorical and continuous variables, respectively), a significant association was considered if p<0, 05. Results: Seventy-eight of 109 patients (72%) had at least one flare. Thirty-one patients had more than one flare and 17 patients had 3 or more flares. The average number of flares/patient was 1.7±1.8 and the mean inter-flare time was 13.4±12.3 months. The flare rate in SLE was 0.52 flares/patient-year of follow-up. The median time to first flare from the date of diagnosis was 2.7±1.2 years. The average SLEDAI score during a flare was 11.8±4.2, at the pre-flare visit was 4.7±3.5 and post-flare visit was 5.3±2.7. The average SLEDAI score in the second flare was higher than first flare (13.7±4.4 versus 10, 3±3, 9, p=0, 07), which reflects a bigger severity. The articular (n=47 patients) and renal flares (n=32 patients) occurred most frequently, followed by hematological (n=25 patients), cutaneous (n=17 patients), pericardium and pleural effusions (n=13) and neurological flares (n=5 patients). Patients with arthritis and cytopenia at the time of diagnosis had a significantly higher flare rate than those who did not (p<0, 05). Patients receiving continuous treatment with hydroxychloroquine and low dosis of corticosteroids had less and milder flares than patients without this treatment (p=0, 001). In our cohort, infections (43%) and discontinuation of therapy (32%) were the main causes of flares. In 25% of the patients the flare etiology was undetermined. Conclusions: In our cohort the flare rate in SLE was 0.52 flares/patient-year of follow-up. Most flares occurred in the first years of disease. The second flare was more severe than first. The articular and hematological involvements at time of diagnosis were more associated with flare rate than other organ involvement. This can be explained by the less intense immunosuppressive therapy in articular and hematological involvement. Continuous treatment with hydroxychloroquine and low dosis of corticosteroids decrease the number and severity of flares. Disclosure of Interest: None Declared